(untitled) (Colombia Medica, 2012)
With the increase of violence and use of firearms in Colombia, we may see more cases of lead poisoning in our environment, and must be prepared to diagnose and treat them. Subtle signs and symptoms as unexplained anemia, gastro-intestinal discomfort and abdominal cramps, and severe as changes in behavior and neurological status, nephropathy, and unexplained death, may be associated with a history of gunshot wounds and projectiles in the human body, and must offer the patient knowledge and management strategies of pathology.